Development of a Geographic Information System–Based Palm Tree Census Tool for Oil Palm Plantations (Case Study: Langkat Regency) - Fragastia, Vidi Agung; Batubara, Rini Oktari; Putra, Armansyah; Afilla, Muhammad Rizky (LPPM Universitas Potensi Utama, 2024)
Oil palm plantations require accurate and timely plant census data to support effective management decisions related to productivity, replanting, and maintenance activities. However, conventional manual census methods are constrained by long processing times, inconsistent data quality, and high susceptibility to human error. These limitations hinder the early identification of abnormal or missing palms and delay operational planning. To address these challenges, this study developed an integrated digital census system using a Web-based Geographic Information System (WebGIS), GPS-enabled Android mobile applications, and drone-based photogrammetry. The research employed the Waterfall Software Development Life Cycle (SDLC), consisting of requirement analysis, system design, implementation, testing, and maintenance. Spatial and non-spatial data were collected through field observations, interviews, GPS coordinates, and UAV imagery. The system was developed using PHP, MySQL, and GIS-based visualization tools, while mobile components utilized GPS navigation to guide field staff in locating abnormal trees. Analysis of census data revealed that 799 out of 47,404 trees (1.68%) were classified as abnormal or missing, a population loss that can significantly reduce potential yield. The GIS-based system demonstrated substantial efficiency improvements, reducing census duration from 7–8 months to 1–2 months in Observation Area 1 and from 4–5 months to 1 month in Observation Area 2. Drone photogrammetry enabled more accurate detection of canopy gaps and validated field measurements. System testing showed that all functional modules performed correctly, and User Acceptance Testing yielded a Cronbach’s Alpha value of 0.821, indicating strong user acceptance and instrument reliability. Overall, the integrated system enhances data accuracy, accelerates census operations, and supports site-specific management in alignment with precision agriculture principles. The results highlight the system’s potential to significantly improve operational efficiency and sustainability in oil palm plantation management.